Mentalization and Attachment Style as Underlying Mechanisms of Linking Collective Efficacy with Parental Self-Efficacy - Osnat Lavenda; Orit Hertz (Social Sciences)
The importance of parental self-efficacy for parental and child well-being is well documented. Many studies demonstrate the significant positive relationship between collective efficacy and self-efficacy. Fewer studies have pointed to the underlying mechanisms of this relationship. The present study aims to fill the knowledge gap by examining two such underlying mechanisms that constitute the essence of the parent–child relationship: pre-mentalization as the parent’s cognitive ability to interpret the child’s internal world and avoidant attachment as the parent’s emotional ability to be in a close relationship with the child. A survey was conducted with 262 married Israeli parents with children under the age of 12. Participants completed self-report questionnaires on collective efficacy, mentalizing ability, avoidant attachment style, and parental self-efficacy. In order to test the mediating role of parental mentalizing ability and avoidant attachment in the association between parental and collective efficacy, a mediation analysis with cross-sectional design was conducted using model 6 PROCESS 3.4 macro for SPSS. Results confirmed the direct relation between collective and parental self-efficacy. Additionally, results indicated a significant indirect effect of this association through low levels of pre-mentalization and avoidant attachment style. The results are discussed in light of the cyclical psychodynamic perspective, with recommendations for interventions that are set to improve parental self-efficacy.